ANALISIS KUALITAS PELAYANAN SWAMEDIKASI DI APOTEK WILAYAH KOTA MANADO MENGGUNAKAN PENDEKATAN MYSTERY CUSTOMER - Lolo, Widya Astuty; Wiyono, Weny Indayany; Mpila, Deby Afriani; Manawan, Fridly; Tatuh, Heru Andika (Sam Ratulangi University, 2025)
Self-medication is an effort by the community to maintain their own health, which can have both positive and negative effects. This study aims to analyse the quality of self-medication services in Manado City using a mystery customer approach. The study was conducted in 96 pharmacies from March to June 2025 using a cross-sectional design. The subjects of this study consisted of pharmacists, pharmacy vocational workers and pharmacy staff. Based on the results of the study, the highest percentages in the demographic data included pharmacy ownership 73.96% (individual), pharmacy location 30,21% (South Manado), time of visit 60,42% (afternoon or evening), disease cases 16,67% (fever), and service providers 46,88% (pharmacy vocational workers). The highest percentages in patient examination and drug information were for whom the drug was intended (57,29%), rational drug use (68,75%), and instructions for use (59,38%). The lowest percentage related to the information provided was on specific medical conditions, one of which was pregnancy (0%). It can be concluded that the quality of self-medication services at pharmacies in the Manado City area varies, mainly depending on the service provider. Keywords: Self-medication, Mystery customer, Patient assessment, Drug selection, Drug information